Bioefficacy of Composite Medicinal Plant Extracts and Gum Arabic on Improving Postharvest Quality in Dragon Fruit - Paa Kwesi Bordoh; Asgar Ali; Matthew Dickinson; Yasmeen Siddiqui; Francisca Aba Ansah (International Journal of Food Science)
Several natural preservative techniques including plant extracts are used to minimize postharvest losses caused by pathogens. Our recent findings elucidated that the application of crude extracts of ginger, turmeric, and “dukung anak” (Phyllanthus niruri Linn.) alone causes phytotoxicity and adversely affects the postharvest quality of dragon fruit, especially at high concentrations. This study investigated the effect of a composite coating of 10% gum arabic (GA) and crude extracts of ginger, turmeric, and “dukung anak” separately at 5, 10, and 15 g L-1 on postharvest quality of dragon fruit stored at 11±2°C, 80% RH for 28 days. After 28 days of cold storage, anthracnose was significantly reduced in fruit coated with 10% GA plus 10 or 15 g L-1 of any of the crude extracts and resolved the problem of phytotoxicity while maintaining the postharvest quality of fruit for 28 days. The reduction of anthracnose was pronounced at 10% GA+10 g L-1 of turmeric extract (38.6%) which was not significantly different at 10% GA+10 g L-1 of ginger extract compared to control (41.3%). Composite coating of 10% GA+10 g L-1 of turmeric extract maintained the postharvest quality of dragon fruit as was evident with a reduction in weight loss (2.53%), delayed degradation of titratable acids (0.15%), and maintained fruit firmness (28.72 N) and the overall acceptability of the fruit after 28 days. We conclude that incorporation of 10% GA with turmeric extract at a high concentration can serve as a potential biofungicide in postharvest management of fresh produced by reducing phytotoxicity while improving the overall acceptability of fruit.